Basal insulin analogues in the diabetes mellitus type 2 control — economic aspects - D. Yu. Belousov; E. V. Afanasyeva (Качественная клиническая практика, 2018)
Economic aspects of insulin analogues — glargine and detemir — in the control of diabetes mellitus type 2 (DM 2) has been prepared in according to needs of the Russian health care system. It has been done that for equal control of DM 2 insulin glargine should be administered in less doses than insulin glargine based on randomized clinical trials results. Results of Russian observational studies of real practice do not show diff erence in doses of both. In the same time glargine has a better effi cacy and safety than detemir based on amount of patients with DM 2 reached targeted levels of control and hypoglycemic events. Clinicaleconomic analysis as well as sensitive analysis did not fi nd any economic advantages of detemir compare with glargine having higher cost for pack. Needed doses diff erentiation of glargine and detemir for equal results of DM 2 control should be taken into account for reimbursement.